Pal Lipoprotein of Escherichia coli Plays a Major Role in Outer Membrane Integrity - Cascales, Eric (American Society for Microbiology, 2002)
The Tol-Pal system of gram-negative bacteria is composed of five proteins. TolA, TolQ, and TolR are inner membrane proteins, TolB is a periplasmic protein, and Pal, the peptidoglycan-associated lipoprotein, is anchored to the outer membrane. In this study, the roles of Pal and major lipoprotein Lpp were compared in Escherichia coli. lpp and tol-pal mutations have previously been found to perturb the outer membrane permeability barrier and to cause the release of periplasmic proteins and the formation of outer membrane vesicles. In this study, we showed that the overproduction of Pal is able to restore the outer membrane integrity of an lpp strain but that overproduced Lpp has no effect in a pal strain. Together with the previously reported observation that overproduced TolA complements an lpp but not a pal strain, these results indicate that the cell envelope integrity is efficiently stabilized by an epistatic Tol-Pal system linking inner and outer membranes. The density of Pal was measured and found to be lower than that of Lpp. However, Pal was present in larger amounts compared to TolA and TolR proteins. The oligomeric state of Pal was determined and a new interaction between Pal and Lpp was demonstrated.